An In Situ Evaluation of the Protective Effect of Nano Eggshell/Titanium Dioxide against Erosive Acids - Stanley Chibuzor Onwubu; Phumlane Selby Mdluli; Shenuka Singh; Sanele Nyembe; Rookmoney Thakur (International Journal of Dentistry)
Objectives. Enamel erosion caused by high consumption of acidic drinks poses a significant public health concern. This study was aimed to determine the protective effect of eggshell-titanium dioxide composite (EB@TiO2) against erosive acids on tooth enamel. Methods. Twenty prepared bovine tooth enamel specimens were randomly assigned to 5 sample groups (n=4): (1) unexposed tooth enamel; (2) exposed tooth enamel + HCI; (3) exposed tooth enamel + HCI + Colgate toothpaste; (4) exposed tooth enamel + HCI + Sensodyne toothpaste; and (5) exposed tooth enamel + HCI + EB@TiO2. The mean roughness value (Rrms) of the exposed and unexposed tooth was measured with atomic force microscope (AFM). Scanning electron microscope (SEM) and Raman spectroscopy techniques were used to evaluate the surface morphology and changes. ANOVA was used to analyze the mean square roughness (Rrms) values for all specimens. Bonferonni correction was used to identify the mean differences among the 5 groups (α=0.05). The Rrms values measured for the unexposed and exposed specimens in HCI alone were statistically significant (P<0.05). Results. No significant differences were found for the unexposed and exposed specimens in HCI + toothpaste and EB@TiO2. The tooth enamel specimens exposed to HCI + Sensodyne had the highest Rrms values, while specimens exposed to HCI + EB@TiO2 had the lowest Rrms values. Conclusions. This study confirms that the investigated toothpaste provides protection against acidic substances. The study results further suggests that EB@TiO2 could be used to provide enhanced protection for tooth enamel.